1993
DOI: 10.1002/mus.880161109
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular transmission in amyotrophic lateral sclerosis

Abstract: The functional and structural characteristics of the neuromuscular junction were studied in anconeus muscle biopsies of 10 patients with amyotrophic lateral sclerosis (ALS). Intracellular recordings revealed decreased amplitudes of miniature endplate potentials (MEPPs). The MEPP frequencies were highly variable in ALS patients but the average MEPP frequency was not different from that of control patients. The mean quantal content of endplate potentials (m), the mean quanta available for immediate release (n), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
98
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 119 publications
(104 citation statements)
references
References 43 publications
6
98
0
Order By: Relevance
“…Tetanic failure was observed in motor units of the medial gastrocnemius (MG) muscle (an ankle extensor) of older homozygote animals that had become extensively weakened by disease progress. A similar phenomenon occurs in human motor neuron disease, where it is observed as decrementing EMG potentials during repetitive activation of motor units (Mulder et al, 1959;Stålberg et al, 1975;Denys and Norris, 1979;Bernstein and Antel, 1981;Maselli et al, 1993). Understanding the underlying mechanisms and finding ways to inhibit tetanic failure or increase unit force are of particular interest, because tetanic failure unquestionably contributes to weakness and weakness is the major problem in motor neuron disease.…”
Section: Abstract: Neuromuscular Disease; Synaptic Transmission; Tramentioning
confidence: 85%
See 3 more Smart Citations
“…Tetanic failure was observed in motor units of the medial gastrocnemius (MG) muscle (an ankle extensor) of older homozygote animals that had become extensively weakened by disease progress. A similar phenomenon occurs in human motor neuron disease, where it is observed as decrementing EMG potentials during repetitive activation of motor units (Mulder et al, 1959;Stålberg et al, 1975;Denys and Norris, 1979;Bernstein and Antel, 1981;Maselli et al, 1993). Understanding the underlying mechanisms and finding ways to inhibit tetanic failure or increase unit force are of particular interest, because tetanic failure unquestionably contributes to weakness and weakness is the major problem in motor neuron disease.…”
Section: Abstract: Neuromuscular Disease; Synaptic Transmission; Tramentioning
confidence: 85%
“…We have suggested that defective neuromuscular synaptic transmission or axonal conduction in motor axon terminal arbors underlies tetanic failure in older HCSMA homozygotes (Pinter et al, 1995), and it seems likely that similar defects underlie decrementing motor unit EMG responses in human motor neuron disease (Maselli et al, 1993). We thus reasoned that increasing neuromuscular transmission might improve motor unit performance in older homozygotes and provide a strategy for the treatment of symptoms.…”
Section: Abstract: Neuromuscular Disease; Synaptic Transmission; Tramentioning
confidence: 99%
See 2 more Smart Citations
“…Collateral reinnervation can compensate for the loss of at least 50 % of the motor neuron pool [25], and probably occurs to some degree until only 5 % of the motor unit pool remains [27,28]. From collateral reinnervation, synaptic sprouts occur such that immature reinnervating end plates form unstable connections with muscle, creating motor unit instability [29]. The effective result of collateral reinnervation is the nonlinear preservation of muscle strength despite falling motor unit number.…”
Section: Need For Assessment Of Motor Unitsmentioning
confidence: 99%